Pilot Observational Cohort study to assess the feasibility of initiating a paediatric cardiac registry - Shakya, Amshu; Shakya, Urmila; Shrestha, Manish; Timala, Rabindra Bhakta; Pradhan, Sidhartha; Shah, Subash Chandra; Panthee, Nirmal; Aryal, Shilpa; Bhandari KC, Vidhata; Thapa, Kul Ratna; Khadka, Devaki (Nepalese Heart Journal, 2025)
Background and Aims: Paediatric cardiac conditions are significant contributors to morbidity and mortality in childhood. Our main aim was systematic collection, storage, analysis, interpretation and reporting of data on paediatric cardiac patients to assess their burden classified by age, gender, residence, ethnicity, diagnosis and treatment and to assess the quality of hospital services. Methods: A quantitative prospective cohort study was performed from January 2024 to June 2024. All children less than 16 years admitted to Shahid Gangalal National Heart Center were included in the study. Information collected in a structured proforma was carefully analysed. Results: Of 656 patients, 374(52.4%) were admitted in medical and 282 (47.6%) in surgery wards. Nearly 19.0% of total admissions were for either consolidation of diagnosis or diagnostic catheterization prior to the subsequent stage of treatment, 403 (61.4%) patients benefited and overall mortality was 69 (10.6%). Acyanotic heart disease was the most common congenital while Rheumatic Heart Disease was the most frequent acquired heart diseases among admitted children. Children with median age 7 months and with Persistent Pulmonary Hypertension, Arterial switch operation and BTT or Central Shunt had higher mortality among others. Conclusions: This study highlights the need for implementation of registry to identify measures to improve paediatric cardiac patients’ care, like routine assessment for malnutrition, proper vaccination, regular audits, staff training, multidisciplinary meetings and recruiting specialists. This study could be a starting point for numerous follow-up studies that are essential for continuous progress.